(untitled) (Educação e Pesquisa, 2010)
Having formative evaluation as its backdrop, and significant learning as its possible horizon, the text aims at exposing conceptual maps as a particularly relevant tool for formative purposes, due to its positive influence on the regulation of teaching and to the self-regulation of learning, and pertinent as a teaching/learning strategy. Revisiting the theoretical framework related to this theme made it possible: (a) to contemplate the usefulness of conceptual maps - used as a teaching and/or evaluating strategy - under different perspectives: that of one who teaches/evaluates, and that of one who learns/is evaluated; (b) to weigh how much making use of conceptual maps means creating alternatives for the organization of knowledge through educative experiences that stimulates not only reflection and the search for understanding and deep processing of information, but also the development of self-regulation, of meta-cognition and of the learning to learn; (c) to rethink the importance of the means employed to evaluate the learning, which cannot be just any means, but those that favor the clear perception of the learning already built as well as of those still under construction, guiding and promoting development activities; and (d) attributing a new meaning to the task of teaching to learn, understood as a constant support in the creation of knowledge through the disclosure of the reasons underlying the difficulties to be overcome.